Pregnancy Young Age with Anemia, Chronic Energy Lack, and Body Index in Mataram City - Catur Esty Pamungkas; Siti Mardiyah WD; Aulia Amini; Dwi Kartika Cahyaningtyas; Evi Diliana Rospia (Jurnal Kebidanan, 2022)
Background: The prevalence of early marriages in West Nusa Tenggara Province in 2010 was 44%, data in West Nusa Tenggara reached 31.32%, ranking 15th out of 34 provinces (BPS, 2017).  Based on the results of 2018, basic health research found three dominant factors that became the focus of BMI, SEZ and anaemia.  PMT in 2018 is 25.2% of all pregnant women.  The proportion of anaemia of pregnant women in Indonesia increased from 2013 by 37.1% to 48.9% in 2018, the age group of pregnant women the majority of anaemia in pregnant women at the age of 15-24 years was 84.6%, the highest proportion of energy chronic deficiency risk in the age group of 15-19 years which is 33.88%, so based on these data the researcher felt the need to do this research. Objective: This study aims to determine the effect of adolescent pregnancy with the incidence of anaemia, SEZ, and BMI in the city of Mataram. Method: This study used an observational design with a cross-sectional design and a sample size of 69 with pregnant women in the city of Mataram, using consecutive sampling techniques.  The statistical test analysis used was bivariate with Chi-Square and multivariate using logistic regression test with a significance level of 5% and 95% confidence interval. Results: The study found no significant relationship between adolescent pregnancy with the incidence of CED and BMI, found a substantial correlation between teenage pregnancy with the prevalence of anaemia.  Multivariate analysis results found a significant association between adolescent pregnancy and the prevalence of anaemia by controlling parity with a value (OR = 4.27; 95% CI: 1,209-15.13).